2016
DOI: 10.1186/s40623-016-0439-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of crustal deformation prior to the 2014 Mt. Ontake eruption by the stacking method

Abstract: The phreatic eruption of Mt. Ontake in central Japan occurred in September 27, 2014. No obvious crustal deformation was observed prior to the eruption, and the magnitudes of other precursor phenomena were very small. In this study, we used the stacking method to detect crustal deformation prior to the eruption. The stacking method is a technique to improve the signal-to-noise ratio by stacking multiple records of crustal deformation. We succeeded in detecting a slight crustal deformation caused by a volume cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…According to their interpretation, decompression caused by the transition of the volcanic fluid to a gaseous phase would propagate simultaneously downwards in the hydrothermal systems and upward, opening cracks beneath the crater. Ascending sources have been identified by other analyses, migration of seismicity (Kato et al, 2015) and ground inflation detected by tiltmeter (Miyaoka and Takagi, 2016). At Merapi, we observe both directions of migration, but shifted in time.…”
Section: Comparison With Other Phreatic Eruptionssupporting
confidence: 75%
“…According to their interpretation, decompression caused by the transition of the volcanic fluid to a gaseous phase would propagate simultaneously downwards in the hydrothermal systems and upward, opening cracks beneath the crater. Ascending sources have been identified by other analyses, migration of seismicity (Kato et al, 2015) and ground inflation detected by tiltmeter (Miyaoka and Takagi, 2016). At Merapi, we observe both directions of migration, but shifted in time.…”
Section: Comparison With Other Phreatic Eruptionssupporting
confidence: 75%
“…GNSS data indicate that the ground inflated by 0.38 × 10 6 m 3 7 min prior to the eruption, although the volume change at depth was comparatively small (Takagi and Onizawa, 2016). Stacking of GNSS data revealed that a small volume change occurred immediately beneath the summit from 1 month prior to the eruption, as well as a small volume increase at depth from 1.5 months before the eruption (Miyaoka and Takagi, 2016). These volume increases were much smaller than those associated with the 2007 eruption (Miyaoka and Takagi, 2016).…”
Section: The 2014 Eruptionmentioning
confidence: 94%
“…Stacking of GNSS data revealed that a small volume change occurred immediately beneath the summit from 1 month prior to the eruption, as well as a small volume increase at depth from 1.5 months before the eruption (Miyaoka and Takagi, 2016). These volume increases were much smaller than those associated with the 2007 eruption (Miyaoka and Takagi, 2016). A very long period (VLP) seismic event occurred 25 s before the eruption, suggesting that preexisting volcanic-tectonic faults ruptured immediately prior to the eruption at depths of 300-1000 m .…”
Section: The 2014 Eruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former would be identified too late in issuing a successful warning while the long-term precursors are based on data too sparse to be useful for near-real-time forecasting 6 . Some mid-term precursors (days to 1 month) were highlighted by re-examining geodetic 9 and seismic data 10 . The ground uplift from geodetic data remained ambiguous, whereas the deviation of the local stress field from seismic data 10 would practically be difficult to implement in most volcano observatories.…”
Section: Introductionmentioning
confidence: 99%